2017
DOI: 10.1155/2017/6137071
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Voluntary Wheel Running on Striatal Dopamine Level and Neurocognitive Behaviors after Molar Loss in Rats

Abstract: The aim of the present study is to evaluate the effect of voluntary wheel running on striatal dopamine level and behavior of cognition and emotion in molar loss rats. Twenty-four Sprague-Dawley rats were enrolled in this study and randomly divided into following 4 groups: control group (C group), molar loss group (ML group), 1-week physical exercise before molar loss group (1W-ML group), and 4-week physical exercise before molar loss group (4W-ML group). The rats both in 4W-ML and 1W-ML groups were placed in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 57 publications
1
5
0
Order By: Relevance
“…Consistently with previous studies, 1 study found that rats induced anxiety-like behavior and decreased exploratory activity in open field tests compared to age-matched controls, 37 our preliminary research reported that the time spent of open arms in the molar loss group was significantly shorter 38 ; the present study used all 3 tests to determine more accurately the presence of anxiety-like behavior in rats with vascular dementia. In addition, our previous experiments also used the open field to discriminate anxiety-like behavior in rats, which produced inconsistent results with our present experimental results.…”
Section: Discussionsupporting
confidence: 90%
“…Consistently with previous studies, 1 study found that rats induced anxiety-like behavior and decreased exploratory activity in open field tests compared to age-matched controls, 37 our preliminary research reported that the time spent of open arms in the molar loss group was significantly shorter 38 ; the present study used all 3 tests to determine more accurately the presence of anxiety-like behavior in rats with vascular dementia. In addition, our previous experiments also used the open field to discriminate anxiety-like behavior in rats, which produced inconsistent results with our present experimental results.…”
Section: Discussionsupporting
confidence: 90%
“…Although most reports prove that physical activity positively affects motor functions (19, 34, 44, 4750, 72) and increases the level of DA in the striatum (19, 73), there are also studies reporting the lack of effects of physical exercise on these parameters (22, 52, 53, 55). For example, Gerecke et al (65) have found that, even though 3 months of training completely protected dopaminergic neurons against MPTP-induced neurotoxicity, the level of DA and its metabolites in the striatum was significantly lower compared to controls.…”
Section: Exercise Induces Recovery Of Motor Function and Neuroprotectmentioning
confidence: 99%
“…HPLC analysis of the brain of rats suffering from tooth loss showed dopamine levels of 26.48 ± 6.67 fmol against normal rat's 55.02 ± 9.05 fmol. After wheel running for one week, the level rose to 50.01 ± 10.52 fmol and after four weeks dopamine level was 52.34 ± 12.54 fmol which was quite close to normal control and indicated wheel running exercise increased dopamine levels [ 82 ]. In literature, other plants are also reported for their involvement in brain neurotransmitters by ethanolic extract of Tylophora indica , increased dopamine levels of 30.655 ± 0.55 × 10 3 units/g in alcohol-toxic albino rats from an initial level of 3.283 ± 0.172 × 10 3 units/g [ 83 ].…”
Section: Resultsmentioning
confidence: 98%